Proceso de atención de enfermería en adulto mayor con insuficiencia renal aguda. - Molina Torres, Kevin Ignacio (2021)
Acute renal failure (ARF) is a clinical syndrome characterized by the gradual or abrupt decrease in renal function, which can occur in a period of time ranging from hours, days to weeks and as a consequence of this the retention of waste substances thus affecting the body. The etiology is multiple because its origin can be from the lower urinary tract, to damage to the kidneys themselves; currently this disease is causing a high prevalence of morbidity and mortality. According to studies carried out by the World Health Organization, until 2020 30% of hospital admissions due to this disease, 5% ended up in Intensive Care Units. The following is a clinical case study of a 66-year-old male patient with a diagnosis of Acute Renal Insufficiency (ARI), admitted to the Basic Hospital of Playas, where the objective of the nursing staff was to develop the Process Nursing Care (PAE), taking into account their pathological antecedents, risk factors, symptoms and altered functional patterns. In addition, the basic needs affected in the patient were analyzed according to the Marjorie Gordon model, in order to satisfy them and achieve a state of comfort in the patient, thus improving their state of health and quality of life.